2017
DOI: 10.1080/17476348.2018.1401926
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and outcomes: a systematic review of palivizumab utilization

Abstract: Palivizumab is a humanized monoclonal antibody used for respiratory syncytial virus (RSV) prophylaxis. RSV is the primary cause of lower respiratory tract infection in children aged <2 years, and can give rise to high-burden hospitalization and respiratory complications in later life. Adherence to a monthly dosing regimen, both in timing and injection number, is essential to sustain therapeutic levels of palivizumab and maintain protective status. Deviation from the approved dosing schedule may reduce the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…Clinical isolates with N262D, K272E/M/Q and S275F/L substitutions in the palivizumab-binding site (antigenic site II, amino acids 258–275) exhibited resistance to neutralization by palivizumab [17]. These mutations were linked to breakthrough infections upon prophylactic treatment [46]. Here, we also report that all RSV-A strains circulating in Lebanon carry an N276S mutation that confer partial resistance to palivizumab and constitute a serious concern for the prevention of RSV infections in at-risk population [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical isolates with N262D, K272E/M/Q and S275F/L substitutions in the palivizumab-binding site (antigenic site II, amino acids 258–275) exhibited resistance to neutralization by palivizumab [17]. These mutations were linked to breakthrough infections upon prophylactic treatment [46]. Here, we also report that all RSV-A strains circulating in Lebanon carry an N276S mutation that confer partial resistance to palivizumab and constitute a serious concern for the prevention of RSV infections in at-risk population [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“… 30 Some authors have shown that home administration of palivizumab may generate better results as it increases compliance and reduces environmental exposures within the hospital of high-risk children. 31 This may be improved by detecting the factors associated with poor adherence, 32 and educational interventions. 33 Nirsevimab, a new monoclonal antibody with an extended half-life for RSV prophylaxis in healthy preterm infants, is being developed to protect infants for an entire RSV season with a single intramuscular dose.…”
Section: Discussionmentioning
confidence: 99%
“…Most therapeutic monoclonal antibodies are used for the treatment of cancer or immunological disorders ( 397 , 398 ). The development of monoclonal antibodies for the prevention and treatment of infectious diseases lags somewhat behind their development for other therapeutic areas, e.g., cancer and autoimmune diseases ( 399 ), and only three monoclonal antibodies have received approval for infectious disease prophylaxis or treatment; palivizumab for prevention of respiratory syncytial virus in high-risk infants ( 400 ); and obiltoxaximab ( 401 ) and raxibacumab ( 402 ) for prophylaxis and treatment of anthrax. The lack of development of mAb for infectious diseases may be because consensus on clinical end-points and definitions on conditions of use are lacking, as well as high costs associated with their development and lack of a cle arly defined market for these products ( 399 ).…”
Section: Other Antifungal Immunotherapeuticsmentioning
confidence: 99%